Laparoscopic repair of bilateral inguinal hernias each containing sigmoid colon in a premature infant - Anastasiya Stasyuk; Christina M. Theodorou; Alana L. Beres (Elsevier, 2021)
Inguinal hernias are rare in the general population but are more frequently seen in premature infants. Risk factors include male gender, small for gestational age, low birth weight and respiratory distress. Infant inguinal hernias most frequently contain small bowel. Other contents can include the appendix and cecum, and rarely, the sigmoid colon. Sigmoid colon as content of inguinal hernia in children has only been reported twice in literature, and in both cases it was unilateral. We present the first reported case of bilateral inguinal hernias containing the sigmoid colon in a premature boy, who additionally had the appendix and the cecum in the right hernia. This is also the first reported laparoscopic repair of such a hernia.